Explaining the perspective of people living with HIV on health‐promoting behaviours based on Pender's model: A directed content analysis - Shahzad Pashaeypoor; Naeimeh Sarkhani; Soheileddin Salmani; Ensiyeh Jamshidi; Raziyeh Maasoumi (Wiley, 2023)
Abstract Aim Health‐promoting behaviours are an important challenge in people living with HIV (PLHIV). Knowing PLHIV's perspective can be helpful for more effective health‐promoting behaviour planning. Therefore, the present study aims to explain PLHIV's perspective on health‐promoting behaviours based on Pender's health‐promotion model. Design A qualitative study with a directed content analysis approach. Methods Altogether, 17 PLHIV referring to the Behavioural Diseases Consultation and Control Center in Tehran, Iran and were selected through purposive sampling. The data were collected through semi‐structured individual interviews and the results were analysed through directed content analysis based on Pender's model. Data management was done by MAXQDA V10. Results Data analysis led to the extraction of 396 codes in 35 subcategories and 15 main categories in 6 constructs of Pender's model, including the perceived benefits (health assurance and optimal disease control), perceived barriers (insufficient knowledge and awareness, lack of motivation, adverse outcomes of the disease and socioeconomic status), perceived self‐efficacy (endeavouring to have a healthy lifestyle, responsibility for one's health and that of others), activity‐related affect (positive and negative feelings), the interpersonal influences (family, friends and relatives and social media) and situational influences (the resources available to the community and community's culture). Patient or Public Contribution In this study, the contribution of PLHIV was used and their perspectives were surveyed. The findings of this study can help policymakers and planners formulate health policies to select the most appropriate strategies and approaches to promoting effective healthy behaviours among PLHIV.